Globalizing Violence: The Mexican Revolution and the First World War - Rinke, Stefan; Kriegesmann, Karina (Jahrbuch für Geschichte Lateinamerikas, 2017)
Without doubt, since its very beginning, the 20th century has been a century of violence. Latin America, too, partook in that experience. This can be illustrated clearly by paying attention to the Mexican Revolution. The protracted civil war in which the various factions fought during many years demanded even more victims per capita than the First World War in all the belligerent European countries. In fact, the Mexican case emphasized that there was no possibility to keep out of the global spiral of violence that during the war years reached a hitherto unknown dimension and went beyond war-torn Europe or single nation states. In order to obtain a more detailed understanding of the interpretive models of the World War developed in Latin America and especially in Mexico, a consideration of the circumstances of cruelty in the subcontinent in the early decade of 1910 appears to be important. This does not mean to establish a causal connection between the developments in Mexico and the World War. However, an analysis of the viewpoint of numerous contemporaries reveals that both events were linked to a world in crisis. From the contemporaries’ perspective, a wave of violence had caught the whole globe and underpinned the end of its self-certainty. This article aims to depict the Mexican perceptions and connotations of the First World War while considering the specific regional circumstances and the interactions between global transformations and local experiences. For Mexico, in particular, the war appeared to be inserted in a period of social revolutionary turmoil and political disturbance, which reached its peak between 1917 and 1919. This process opened up new spaces for understanding the role of the nation as well as for its position in a world which was profoundly changing.